2007
DOI: 10.1128/ec.00199-07
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Candida albicans Sfl1 in Hyphal Development

Abstract: The ability to switch between different morphological forms is an important feature of Candida albicans and is relevant to its pathogenesis. Many conserved positive and negative transcription factors are involved in morphogenetic regulation of the two dimorphic fungi Candida albicans and Saccharomyces cerevisiae. In S. cerevisiae, the transcriptional repressor Sfl1 and the activator Flo8 function antagonistically in invasive and filamentous growth. We have previously reported that Candida albicans Flo8 is a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
65
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 49 publications
(51 reference statements)
5
65
1
Order By: Relevance
“…Consistent with a transcriptional regulatory function, an Sfl1p-GFP fusion localized to the nucleus, while one hybrid lacZ reporter analyses in C. albicans correlated with a repressor function [37]. Importantly, either deletion or overexpression of SFL1 attenuated C. albicans virulence in a mouse model of systemic infection [38]. On the other hand, we and others have shown that deletion of SFL2 impaired filamentation in response to different cues, whereas SFL2 overexpression promoted hyphal growth, even under non hyphae-stimulating conditions [39][40][41].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Consistent with a transcriptional regulatory function, an Sfl1p-GFP fusion localized to the nucleus, while one hybrid lacZ reporter analyses in C. albicans correlated with a repressor function [37]. Importantly, either deletion or overexpression of SFL1 attenuated C. albicans virulence in a mouse model of systemic infection [38]. On the other hand, we and others have shown that deletion of SFL2 impaired filamentation in response to different cues, whereas SFL2 overexpression promoted hyphal growth, even under non hyphae-stimulating conditions [39][40][41].…”
Section: Introductionmentioning
confidence: 74%
“…Interestingly, the C. albicans genome encodes two structural homologs of ScSfl1p, namely Sfl1p and Sfl2p [37][38][39][40]. Either SFL1 or SFL2 functionally complement an S. cerevisiae sfl1 mutation [38,39] and encode important regulators of morphogenesis and virulence in C. albicans [37][38][39][40]. Intriguingly, although sharing structural homologies, Sfl1p and Sfl2p have antagonistic functions: while Sfl1p acts as a negative regulator of hyphal development, Sfl2p acts as a positive regulator of this process [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations